Association between increased FVIIa-antithrombin complex/FVIIa ratio and pre-eclampsia. (15th April 2013) - Spiezia, Luca; Visentin, Silvia; Radu, Claudia; Bon, Maria; Woodhams, Barry; Cosmi, Erich; Simioni, Paolo
Abstract: Objective : Activated factor VII-antithrombin (FVIIa-AT) complexes can be used to reflect the degree of intravascular exposure of tissue factor (TF). The aim of the present case-control study was to evaluate FVIIa-AT plasma levels during normal pregnancy and in pre-eclampsia (PE). Methods : One hundred and five pregnant women were enrolled and namely n = 30 in the first (T1), n = 30 in the second (T2), n = 30 in the third (T3) trimester of pregnancy and n = 15 with PE. FVIIa-AT complexes were determined using a specific ELISA (Diagnostica Stago, Asnieres, France). Results : FVIIa-AT complexes were significantly higher in pregnant (119 ± 24 pM) than in healthy (102 ± 12 pM, p = 0.001) women. No difference in FVIIa-AT levels between T3 women and with PE was observed. Interestingly, women with PE had significantly higher FVIIa-AT/FVIIa ratio than women during T3 (2.01 ± 0.44 versus 1.50 ± 0.29, p = 0.001). Conclusion : FVIIa-AT complexes plasma levels differed significantly between normal pregnancy and non-pregnant women. Moreover, FVIIa-AT/FVIIa ratio was higher in patients with PE than in normal pregnant women.